Theory of mind: network of complex processes woven into the intersubjective experience - Bedoya-Gallego, Diana Marcela; González-Gaviria, Maira Alejandra; Palacio-Sañudo , Jorge Enrique (Revista Colombiana de Ciencias Sociales, 2024)
This paper aims to contribute to the reflection that expands and makes explicit the aspects of early motherchild bonding that favor the development of Theory of Mind (ToM). For this purpose, first, we start from the conceptualization of ToM and its understanding from the Theory of Theories and Simulation Theory, as they have been identified as the most important theoretical models that explain one of the most relevant differential capacities of the human species. Subsequently, it is proposed that this capacity emerges in the bonding context, since due to its complexity it constitutes an evolutionary advantage that favors the establishment of the social bond; for this purpose, the developments of the Attachment Theory are used. The content analysis carried out allows us to recognize that treating the child as a mental agent (intentional and with individuality) and tending to use terms of mental state in discourse, play a fundamental role in the development of children’s capacity to understand other minds, so that rather than entering into the debate of internalist or externalist perspectives on the development of ToM, the value of intersubjective experience is highlighted.